The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1186/1471-2334-11-127
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and associated risk factors in a cohort of tuberculosis patients treated under DOTS programme in Addis Ababa, Ethiopia

Abstract: BackgroundTuberculosis (TB) is the leading cause of mortality among infectious diseases worldwide. Ninty five percent of TB cases and 98% of deaths due to TB occur in developing countries. Globally, the mortality rate has declined with the introduction of effective anti TB chemotherapy. Nevertheless, some patients with active TB still die while on treatment for their disease. In Ethiopia, little is known on survival and risk factors for mortality among a cohort of TB patients. The objective of the study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
46
6
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 21 publications
21
46
6
2
Order By: Relevance
“…In agreement with previous studies done in different part of the world, in the present study, older ages, smear negative [12,15] and HIV positive [7,10] pulmonary TB patients were more likely to die than their counter parts.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with previous studies done in different part of the world, in the present study, older ages, smear negative [12,15] and HIV positive [7,10] pulmonary TB patients were more likely to die than their counter parts.…”
Section: Discussionsupporting
confidence: 82%
“…The overall death rates of TB patients in this study was found to be 82 (9%), which is greater than 3.3 % in Northwest Ethiopia [25], 3.7% in a study done in Addis Ababa [12], 3.6% in Gambella [20] and 2.6% in Southern Ethiopia [8] but slightly lower than a study conducted in Gondar University Hospital [15] with death rate of 10.1%.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…One study in Addis Ababa revealed that body weight at initiation of anti-TB treatment (<35 kg) was a significant risk factor of death during antituberculosis treatment period [28]. This difference may be related to the classification of body weight at initiation of anti-TB treatment; in this study body weight classification is based on WHO standard treatment guideline but a study conducted in Addis Ababa used another type of body weight classification.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, results from studies in Ethiopia ranged from 26% to 94% [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The previous report of TB defaulter, failure, and death rates in Ethiopia ranged from 0.6% to 18.3% [8][9][10][11][12][13][14][15][16][17][18], 0.2% to 18.6% [8][9][10][11]15], and 2.6% to 10.1% [8-10, 12,15,16,19,20], respectively.…”
Section: Introductionmentioning
confidence: 99%